2010
DOI: 10.1088/1468-6996/11/4/045001
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of methane adsorption onto boron nitride and carbon nanotubes

Abstract: Methane adsorption onto single-wall boron nitride nanotubes (BNNTs) and carbon nanotubes (CNTs) was studied using the density functional theory within the generalized gradient approximation. The structural optimization of several bonding configurations for a CH 4 molecule approaching the outer surface of the (8,0) BNNT and (8,0) CNT shows that the CH 4 molecule is preferentially adsorbed onto the CNT with a binding energy of −2.84 kcal mol −1 . A comparative study of nanotubes with different diameters (curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…However, CNTs have the potential to be developed as a gas sensing material due to their inherent properties such as their small size, great strength, high electrical, and thermal conductivity, and high specific surface area [10][11][12][13][14][15][16]. Similar to CNTs, the effects of gas adsorption on the electronic properties of BNNTs have attracted certain attention [17][18][19][20][21][22][23]. For example, the adsorption of molecular hydrogen on BNNTs has been studied by using density functional theory (DFT) [17,18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, CNTs have the potential to be developed as a gas sensing material due to their inherent properties such as their small size, great strength, high electrical, and thermal conductivity, and high specific surface area [10][11][12][13][14][15][16]. Similar to CNTs, the effects of gas adsorption on the electronic properties of BNNTs have attracted certain attention [17][18][19][20][21][22][23]. For example, the adsorption of molecular hydrogen on BNNTs has been studied by using density functional theory (DFT) [17,18].…”
mentioning
confidence: 99%
“…They discussed that at incident energies below 14 eV hydrogen bounces off the BNNT wall and at incident energies between 14 and 22 eV each hydrogen molecule is dissociated at the exterior wall. Using DFT within the generalized gradient approximation, methane adsorption onto BNNT and CNT is considered by Ganji et al [20]. They showed that the methane molecule is preferentially adsorbed onto the CNT with a binding energy of −2.84 kcal/mol.…”
mentioning
confidence: 99%
“…This was due to the fact that high bonding energy among LPG atoms allows limited electron transfer from LPG molecules to the CNTs [51]. In our experiment, the -Fe 2 O 3 /CNTs-based LPG sensor's improved response was achieved by converting Fe, which served as catalyst for the growth of CNTs, toFe 2 O 3 , causing an increase in LPG active sites in the CNTs.…”
Section: Lpg Sensing Mechanismmentioning
confidence: 74%
“…Figure 5(d) presents the sensor response, and -Fe 2 O 3 / CNT films showed the maximum in response along with fast response/recovery time, while as-grown CNT and purified CNT films had a low response. This was due to the fact that high bonding energy among LPG atoms allows limited electron transfer from LPG molecules to the CNTs [51]. However, the purified CNTs had a quick response/recovery time because of the highly purified CNTs than that of CNT films.…”
Section: Sensing Properties Of Lpg Sensors the Sensor Response To Lpmentioning
confidence: 99%
“…As distinct from the binding energy (−0 543 eV), the strong interaction of Al with B 24 N 24 leads to significant electron transfer from the metal to the B 24 N 24 nanocage. [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] Table I shows the levels of energy for the empty B 24 N 24 and the endohedral B 24 N 24 nanocages. It was clearly found that the empty B 24 N 24 nanocage does not show the effects of spin splitting so the gap of energy between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of B 24 N 24 is the same (4.431 eV) for the majority spin or the minority spin.…”
Section: Resultsmentioning
confidence: 99%